(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
The upsurge and growth in the uptake of social media has had a profound impact on journalism as it has traditionally been practised. Social media has permeated all aspects of human activities and brought with it negative as well as positive effects on society. It has not only affected the way we communicate, socialize and work, but also view the world. This new media has affected the way the profession of journalism is practised. It has made it possible for persons without any training in journalism – bloggers to write and post stories without any censorship. Some of the stories are sensational fabrications lacking facts and professional editorial input – they are fake news. Social media has enabled persons without any publishing knowledge to publish newspapers, magazines and books without going through the editorial vetting process. It has enabled journalism to become a free-for-all trade where anyone who is IT savvy can write and post content that will be readily consumed by an international audience. This is done in utter disregard of journalistic code of practice and is devoid of professional ethics. The end result has been a plethora of publications which are poorly written, poorly edited and utterly lacking in authenticity and artistic creativity as we have always known it. Not all is bleak however. Social media has come with a number of advantages that have impacted the way we work, behave and relate. Social Media has had a positive effect on society; be it in business, or in education, it has helped us to stay updated on current affairs and new developments, communication and health. Through social media, there has been an increase in the uptake of skills, new technology and information dissemination. It has revolutionized the work of journalism and made communication easier and faster. This paper has used library and internet research to evaluate the impact of social media on journalism and to suggest possible solutions to the problem of proliferation of fake news.